Faciocervical Reconstruction Using a Large Expanded Forehead Island Flap Grafted Using a Microsurgical Technique for Burned Cicatricial Contracture Correction. Issue 7 (October 2018) - Han, Bing; Fan, Jincai; Liu, Liqiang; Tian, Jia; Gan, Cheng; Yang, Zengjie; Jiao, Hu; Zhang, Tiran; Liu, Zheng; Zhang, Hua
Abstract : Abstract: Extrinsic cicatricial contracture is still one of the most common and frustrating complications in the faciocervical area after severe burns. Because of these contractured scars, patients not only suffer from aesthetic issues but also local dysfunction, especially when it comes to the faciocervical region. Esthetical and functional reconstruction of these regions remains a great challenge for reconstructive surgeons. This report presents a 28-year-old man with postburn mentocervical adhesion treated successfully with a large expanded forehead island flap. Cosmetic and functional results have been achieved in this patient during long-term follow-ups.